2014
DOI: 10.1038/nclimate2353
|View full text |Cite
|
Sign up to set email alerts
|

Importance of food-demand management for climate mitigation

Abstract: Recent studies show that current trends in yield improvement will not be sufficient to meet projected global food demand in 2050, and suggest that a further expansion of agricultural area will be required. However, agriculture is the main driver of losses of biodiversity and a major contributor to climate change and pollution, and so further expansion is undesirable. The usual proposed alternativeintensification with increased resource use-also has negative effects. It is therefore imperative to find ways to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
446
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 617 publications
(511 citation statements)
references
References 30 publications
15
446
0
9
Order By: Relevance
“…In this context, both the choice of policy instruments and the way in which governments react to pressures to avoid or deflect the costs of mitigation may have the potential for conflict with World Trade Organisation (WTO) trade rules (Blandford & Josling, 2009). B Changes in consumer diets and decreases in food waste are essential to deliver emissions reductions and provide global food security in 2050 as recent global studies suggest (Bajželj et al, 2014;Tilman & Clark, 2014). Similar observations have been confirmed for Europe, especially with respect to livestock products (Bellarby et al, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…In this context, both the choice of policy instruments and the way in which governments react to pressures to avoid or deflect the costs of mitigation may have the potential for conflict with World Trade Organisation (WTO) trade rules (Blandford & Josling, 2009). B Changes in consumer diets and decreases in food waste are essential to deliver emissions reductions and provide global food security in 2050 as recent global studies suggest (Bajželj et al, 2014;Tilman & Clark, 2014). Similar observations have been confirmed for Europe, especially with respect to livestock products (Bellarby et al, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…To explore the scope for combining emissions reduction strategies, we next assessed two promising demand-side measures 14 implemented alongside land sparing. We quantified the effect of replacing some animal products in the diet with vegetarian substitutes (Fig.…”
mentioning
confidence: 99%
“…Agricultural expansion was assumed to be responsible for meeting additional demand until industrial fertilisers became available, with the relative contribution of expansion assumed to decline to 22 % by 1999 (12) , and intensification through industrial fertilisation, irrigation and mechanisation becoming the dominant means to meet growing demand. The future failure of intensification to meet increasing food demand to 2050 is demonstrated by Bajželj et al (27) , but the relative contribution of demand management and intensification in the future remains unquantified, and should be viewed as schematic rather than quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown the importance of demand-side measures (24)(25)(26) . Recently, a new study has quantified the potential role of sustainable intensification in meeting global food requirements, and it showed that sustainable intensification alone cannot deliver food security; demand management appears to be essential (27) . Bajželj et al (27) found that delivering more food for 2050 by sustainable intensification, through yield gap closure, could reduce baseline cropland area, forest area loss, total greenhouse gas emissions and water use relative to a baseline of current yield trend, but would still lead to expanded agricultural area.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 1 more Smart Citation